The influence of tax knowledge, taxpayer awareness, and income on compliance in paying land and building tax in Rejosari Village, Pringsewu District - Citra Adista; Andi Mulyono (Institute of Accounting Research and Novation (IARN), 2025)
This study examines the impact of tax knowledge, taxpayer awareness, and income on compliance in paying Land and Building Tax (PBB) in Rejosari Village, Pringsewu District. As a key source of local revenue, Land and Building Tax relies heavily on public participation. However, the current level of taxpayer compliance remains suboptimal, necessitating an investigation into the underlying influencing factors. Using a quantitative approach, the research population includes 2,545 taxpayers, with a sample of 97 respondents selected through random sampling via the Slovin formula. Data were gathered using a Google Forms-based questionnaire and analyzed through multiple linear regression analysis with SPSS version 25. The results demonstrate that tax knowledge, taxpayer awareness, and income each have a positive and significant effect on tax compliance. These findings suggest that improving taxpayers' understanding, legal awareness, and financial capacity can enhance compliance. The study recommends that village authorities and relevant institutions intensify tax education and promote collective awareness to sustainably increase tax revenue.